MODERN TRENDS IN HUMANITIES AND SOCIAL SCIENCES: WITH SPECIAL FOCUS ON COVID-19 SCENARIOS AND IMPLEMENTATION OF LAWS - Azra Qadir (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
A corona virus is a kind of common virus that causes an infection in your nose, sinuses or upper throat. SARS-Cov2, identified in Wuhan (China) for the first time in December 2019 is a new viral strain which has not been introduced in humans previously. It can be transmitted by air and via direct and indirect contact however its frequent way to spread is via droplets. Covid-19 has already surpassed the death toll of more recent outbreak of Ebola, swine flu, dengue, Congo virus, MERS, SARS, black fungus in India and lambada in the European countries. Fatalities in Pakistan have as of today hit 60. WHO is urging all countries to prepare for the emergency response system, increasing capacity to detect any care for patient ensuring hospitals to save the lives of people in covid19 pandemic. Pakistan spends 2% of its GDP on healthcare against a global average of 10%. Pakistan shares borders with China, Iran, Afghanistan and India also. Cases are reported in huge numbers in last few days. Laws are implemented as ? WHO declares the Covid-19 as a public health emergency of international concern on 30th January 2019 with no travel and trade restrictions were recommended. ? Corona virus (Covid-19) home care precaution. ? Covid-19 pandemic, prevention and protection measures to be adopted at work place. ? Corona virus and covid-19. What you should know. ? Corona virus prevention, 12 tips and strategies. ? Pakistan and institution measures in response to covid-19 KPMG ? 1.2 trillion and supplementary grant of Rs. 100 billion for the "Residual/Emergency Relief Fund". ? Important steps taken by the Government as National Action Plan for corona virus disease Covid-19 Pakistan. Contents explain as Overview, National action plan policy, Vision, Aims, Objectives, Strategic determinants/goals, Operations, Board implementation arrangements, Monitoring and evolution and Conclusion. These points are discussed all arrangement about the pandemic and taking steps for stake holders of the state. ? How to protect yourself? ? The Punjab occupational safety and health Act 2019 ? The Punjab infectious disease (Prevention and Control) Act 2020 ? Annexure A to M totally deals with the pandemic arrangement, healthcare, quarantine’s sops, testing, sampling, burial guidelines, social distancing and advisory on mitigation strategies of covid-19.